Comparative Transcriptomic Analyses of Antibiotic-Treated and Normally Reared Bactrocera dorsalis Reveals a Possible Gut Self-Immunity Mechanism - Fu, Jiajin; Zeng, Lingyu; Zheng, Linyu; Bai, Zhenzhen; Li, Zhihong; Liu, Lijun (Frontiers in Cell and Developmental Biology, 2021)
Bactrocera dorsalis (Hendel) is a notorious agricultural pest worldwide, and its prevention and control have been widely studied. Bacteria in the midgut of B. dorsalis help improve host insecticide resistance and environmental adaption, regulate growth and development, and affect male mating selection, among other functions. Insects have an effective gut defense system that maintains self-immunity and the balance among microorganisms in the gut, in addition to stabilizing the diversity among the gut symbiotic bacteria. However, the detailed regulatory mechanisms governing the gut bacteria and self-immunity are still unclear in oriental fruit flies. In this study, the diversity of the gut symbiotic bacteria in B. dorsalis was altered by feeding host fruit flies antibiotics, and the function of the gut bacteria was predicted. Then, a database of the intestinal transcriptome of the host fruit fly was established and analyzed using the Illumina HiSeq Platform. The gut bacteria shifted from gram-negative to gram-positive after antibiotic feeding. Antibiotics lead to a reduction in gut bacteria, particularly gram-positive bacteria, which ultimately reduced the reproduction of the host flies. Ten immunity-related genes that were differentially expressed in the response to intestinal bacterial community changes were selected for qRT-PCR validation. Peptidoglycan-recognition protein SC2 gene (PGRP-SC2) was one of the 10 immunity-related genes analyzed. The differential expression of PGRP-SC2 was the most significant, which confirms that PGRP-SC2 may affect immunity of B. dorsalis toward gut bacteria.